2019
DOI: 10.1177/0300060519871812
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects and risk factors of lupus nephritis: a retrospective study of 156 adult patients

Abstract: Objective To analyze the clinical manifestations, laboratory indexes, disease activity, and pathological types of lupus nephritis (LN) in adult patients. Methods We retrospectively analyzed the clinical manifestations, laboratory indexes, and pathological classifications of 156 adult patients first diagnosed with LN between July 2013 and November 2017. Patients were categorized according to the following criteria: active or inactive LN, LN with or without renal damage, and mild or severe LN. Results Immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Our results were consistent with previous studies showing a higher prevalence of malar rash [17], serositis [18], pulmonitis [19], lymphadenopathy [20], necrotizing vasculitis [21], higher SLEDAI score [22], and lower prevalence of Raynaud's phenomenon [23], Sjogren's syndrome [24], and peripheral nervous system manifestations [25] in LN patients. SLE patients with LN had a higher frequency of arterial or venous thrombosis than non-renal SLE patients, while no differences were observed in regard to antiphospholipid syndrome and antiphospholipid antibodies positivity in line with literature data [26].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with previous studies showing a higher prevalence of malar rash [17], serositis [18], pulmonitis [19], lymphadenopathy [20], necrotizing vasculitis [21], higher SLEDAI score [22], and lower prevalence of Raynaud's phenomenon [23], Sjogren's syndrome [24], and peripheral nervous system manifestations [25] in LN patients. SLE patients with LN had a higher frequency of arterial or venous thrombosis than non-renal SLE patients, while no differences were observed in regard to antiphospholipid syndrome and antiphospholipid antibodies positivity in line with literature data [26].…”
supporting
confidence: 93%
“…Besides, a higher proportion of LN patients had necrotizing vasculitis (9.2% vs 2.0%) and a history of arterial/venous thrombosis (9.7% vs 2.5%) compared to patients without kidney involvement. In addition, the SLEDAI score of LN patients was significantly higher (14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) points vs 8 (4-14) points, p<0.001) than in non-renal SLE patients. The frequency of anemia, leukopenia, and thrombocytopenia did not differ significantly between the groups.…”
mentioning
confidence: 87%
“…Increased urea levels are associated with impaired kidney function. About 50% of SLE patients have kidney damage including glomerular and tubulointerstitial pathology, and 100% of SLE patients have varying degrees of renal pathological changes. , Previous studies have shown that in female MRL/lpr mice, the urinary protein creatinine ratio, which reflects the degree of kidney damage, was significantly increased at 13 weeks of age . This is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, low albumin was also associated with depression. Low serum albumin correlates with kidney disease [ 23 ] and outcomes in lupus nephritis [ 24 ]. These kidney findings are especially interesting given that none of the JSLE patients were diagnosed with lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%